PENGARUH BRAND IMAGE, POINT OF DIFFERENT, DAN POINT OF PARITY TERHADAP BRAND LOYALTY iPHONE PADA KONSUMEN DI JAKARTA UTARA - Sarah Azalia Cosina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
In today’s era, it is very easy to access various information whether from printmedia or electronic media. But, consumers would certainly choose to search forinformation with easier access media like smartphone. One of the smartphonebrands that used by many is iPhone by Apple Inc. There are many factors that leadconsumers to choose to use iPhone smartphone. At this opportunity, the authorchooses to do research on brand image, point of different, and point of parityfactors on iPhone brand loyalty among consumers in Jakarta Utara. The object of this study is iPhone smartphone. The sample in this study is the people who useiPhone. The method used for data collecting is by distributing questionnairesthrough Google Form to collect 115 respondents. The sampling technique used inthis study is non-probability sampling with judgemental sampling with criteriaconsumers who have been using iPhone for the past three months and at least 16years old. The data analyzing technique that used in this study is multipleregression by SPSS. This study shows that brand image and point of different havea positive and significant impact on iPhone brand loyalty while point of paritydoesn’t have a positive and significant impact on iPhone brand loyalty